2020
DOI: 10.3390/ijerph17041269
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotics, Trace Metals and Genetics in the Pathogenesis of Tauopathies

Abstract: Tauopathies are a disease group characterized by either pathological accumulation or release of fragments of hyperphosphorylated tau proteins originating from the central nervous system. The tau hypotheses of Parkinson’s and Alzheimer’s diseases contain a clinically diverse spectrum of tauopathies. Studies of case records of various tauopathies may reveal clinical phenotype characteristics of the disease. In addition, improved understanding of different tauopathies would disclose environmental factors, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…However, dysfunction of the ApoE receptors LRP1 and LRP8 may represent causal factors for the observed microtubule derangement by disrupting the supply of essential nutrients such as cholesterol and selenium. Apparently, tau hyperphosphorylation occurring in AD compromises its normal functions and leads to formation of insoluble neurofibrillary tangles forming bundles of protein filaments [51]. Phosphorylating kinases and de-phosphorylating phosphatases in tandem regulate this process.…”
Section: Tau Hyperphosphorylation In Admentioning
confidence: 99%
“…However, dysfunction of the ApoE receptors LRP1 and LRP8 may represent causal factors for the observed microtubule derangement by disrupting the supply of essential nutrients such as cholesterol and selenium. Apparently, tau hyperphosphorylation occurring in AD compromises its normal functions and leads to formation of insoluble neurofibrillary tangles forming bundles of protein filaments [51]. Phosphorylating kinases and de-phosphorylating phosphatases in tandem regulate this process.…”
Section: Tau Hyperphosphorylation In Admentioning
confidence: 99%
“…APOE4 has the ability to bind β-amyloid and plays a role in Aβ conversion from monomeric and non-toxic forms to oligomers and fibrils (Castano et al., 1995). In addition, numerous studies have demonstrated that exposure to some environmental factors, such as xenobiotics and lifestyle stress, also contribute to the progression of sporadic AD (Aaseth et al., 2020; Madore et al., 2020; Shi et al., 2020).…”
Section: Alzheimer’s Diseasementioning
confidence: 99%